A STUDY OF ROMANIAN CONSUMERS' FOOD PURCHASING, CONSUMPTION BEHAVIOR, AND MOTIVATION TO AVOID AND REDUCE FOOD WASTE - Mirela STANCIU; Cristina DANCIU; Iuliana ANTONIE; Camelia SAVA; Anca TULBURE; Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The issue of preventing and reducing food waste (FW) at the household level is of paramount importance and must be analyzed in relation to food purchasing, handling, and consumption habits. This study examines food purchasing and consumption habits in the context of food waste avoidance, among consumers in Romania. An online survey (N = 369, 67.21% women) was conducted to analyze food purchasing and consumption behavior, shopping planning routines, and food waste avoidance behavior. The average age of the respondents was 30.22 years. The collected data was analyzed, processed, and interpreted. Main findings: In 76% of the households surveyed, some of the food needed is produced in the household. The primary source of food supply is the hypermarket, regardless of the food category. About 84.55% of consumers cook at home very frequently and eat meals with their families. The highest scores for shopping planning routines were recorded for the habit of checking food stocks (3.82) and creating a shopping list (3.32). Nearly half of the respondents are responsible for both food purchases and cooking at home. Personal motivation for reducing food waste primarily involves assuming social responsibility (3.92), followed by concern for the environment. Over 87% of consumers believe that a national policy is necessary to implement educational and informational programs and projects aimed at preventing and reducing food waste.